Learning Method with Table-top Disaster Exercise Can Improve Nursing Students' Knowledge and Skill: Literature Review - Andika, I Putu Juni; Yahya Christina, Tri; Safaruddin, Safaruddin; Sriwiyati, Lilik (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Nurses must now strengthen their duties as disaster nurses in emergency response due to the rising frequency of disasters. This scenario can be addressed by improving nursing students' initial readiness through disaster education; hence, this proposal calls for new approaches to creative and successful disaster learning. Simulation using a Tabletop Disaster Exercise (TDE) is one of the suggested teaching strategies. The objective of this research is to determine whether the TDE learning method can enhance nursing students' knowledge. This literature uses inclusion and exclusion criteria, articles obtained, reviewed, and obtained from databases, namely, Google Scholar (2020–2024), PubMed (2020–2024), and Wiley Online Library (2020–2024). The search strategy with terms used in English is as follows: TDE and Nursing Student and Knowledge. The year the literary source is taken from 2020 until 2024. Search strategy with the keyword “TDE and Knowlegde and skill and nursing student,” and in Bahasa Indonesia “metode dan TDE dan pengetahuan dan keterampilan dan mahasiswa keperawatan .” This is to make sure all the articles obtained are relevant and appropriate, then the full text is downloaded and saved. The initial identification of titles and abstracts in PubMed received 118 articles, in Wiley Online Library received 136 articles, and in Google Scholar received 4,311 articles, totaling 4,565 articles. The results of the literature review from 13 articles state that the TDE method can significantly improve nursing students' knowledge and skills in disaster management. All the discussed articles state that the use of tabletop disaster training media among nursing students in the context of disaster nursing can enhance their knowledge and skills. In addition, they can also experience it as if it were the real world.